Effects of Calcium Regulating Hormones on Osteoclast-Like Cell Formation in Hen Medullary Bone Marrow Culture - Toshie Sugiyama; Midori Sakurai; Shinji Hiyama; Seiji Kusuhara (The Journal of Poultry Science, 2004)
In order to examine the effects of the calcium regulating hormones on the differentiation of hen medullary bone osteoclasts, isolated medullary bone marrow cells were cultured for 8 days in media including parathyroid hormone (PTH), 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] or 17β-estradiol (E2), respectively. After 8 days of culture, tartrate-resistant acid phosphatase (TRAP) activity, a marker for osteoclasts, was enzymehistochemically detected on the cultured marrow cells and these cells were also stained with Mayer’s hematoxylin. Thereafter, TRAP-positive multinuclear cells were counted as osteoclast-like cells, and the effects of the calcium regulating hormones on the osteoclast differentiation from medullary bone marrow cells were indicated as the percentage (%) of the controls when vehicle was added in place of the hormones. As a result, treatment with PTH or 1,25(OH)2D3 significantly stimulated the differentiation of osteoclast-like cells, up to 218.3% or 159.2%, respectively. On the other hand, E2 treatment resulted in a moderate, but not significant, suppression of differentiation (85.8% of controls). These results indicate that PTH and 1,25(OH)2D3 stimulate medullary bone osteoclast differentiation, but E2 is likely inhibitory.